Possíveis efeitos da mídia impressa sobre a inclusão de estímulos em classes de estímulos equivalentes previamente formadas: um estudo exploratório - Silva, Camila Maria Silveira da (2010)
The purpose of the present study was the development of a methodology aimed at evaluating the impact of news from written media upon the behavior of readers, in terms of inclusion of stimuli on classes of previously formed equivalent stimuli. Two aspects related to this aim deserved special attention in the planning of the research: the first one concerns the training procedure which would be more adequate to generate equivalent classes of stimuli; the second one concerns the use of other measures which could evaluate the impact of news, such as bipolar scales or semantic differentials. Three issues guided the research: 1) Is it possible to evaluate the impact of written media upon behavior once this impact is defined by the inclusion of a pseudoword inserted in a piece of news on classes of previously formed equivalent stimuli and with an also previously established behavioral function? 2) Could different sequences of training produce different results in the formation of classes of equivalent stimuli with an also previously established behavioral function? 3) Would a pseudoword which had never before been related to any abstract stimulus having, though, been presented through some piece of news be evaluated by the participants through bipolar scales in a similar way as if this pseudoword had been inserted in classes of equivalent stimuli with an also previously established behavioral function?Three experiments were developed to answer these questions. Experiment 1 initially involved 40 university students. The 32 who managed to complete it showed emergent relations. Half the participants were submitted to a specific sequence of training, which began with simple discrimination. The other half was submitted to another sequence, which began with conditional discrimination. The two groups undertook both procedures (simple and conditional discrimination), involving three groups of stimuli to be established as classes in the conditional discrimination, and two groups of the same stimuli to be established as S+ and S-, in simple discrimination. Experiment 2 involved the 32 University students, who had showed emergent relations on the previous experiment, thus having established three classes of stimuli: S+, S- and neutral (not trained in simple discrimination). These participants were submitted to matching to sample tests to verify the inclusion or non inclusion of a pseudoword, which had appeared in pieces of news they had read, in a certain class of stimuli. 24 out of the 32 participants went through the baseline. Eigth of them did not go through this phase. In Experiment 3, it was asked of 10 amongst the 32 participants to evaluate, in bipolar scales, the pseudoword that appeared in the news. The results were, then, compared to the results of the same participants during the matching to sample. The results demonstrated that, in Experiment 1, the training sequence that started with simple discrimination seemed to facilitate the performance of the participants in the first AB block of conditional discrimination, but not in the first BC block. Besides, conditional discrimination also appears to have facilitated the performance in simple discrimination. In Experiment 2, half the participants which went through the baseline altered the inclusion of the pseudoword which appeared in the news, in at least one of the conditions to which they were submitted. The other half kept the original inclusion. On the other hand, to most participants who did not go through this phase, the first inclusion of the pseudoword, which took place immediately after the reading of the news, was not altered. Finally, in Experiment 3 there were several discrepancies amongst the results obtained through the bipolar scales and the results obtained through the matching to sample tests